Factores sociodemográficos, individuales y contextuales como predictores del consumo de marihuana según género en la población de 12 a 65 años de Lima Metropolitana: análisis de la base de datos de DEVIDA 2013 - Cabanillas Rojas, William Eugenio (2021)
This research has the objective of to estimate the predictive value of gender-specific sociodemographic, individual and contextual factors for the marijuana use in the last year in the general population of Lima. The study was cross-sectional descriptive and analytical using the database of the Study on Drug Prevention and Consumption in the General Population of Metropolitan Lima and Callao- 2013 conducted by the National Commission for Development and Life without Drugs (DEVIDA). The sample consisted of 18,562 participants from 12 to 65 years randomly selected. Descriptive analyzes and logistic regressions was used for complex samples. In general, statistically significant differences were found between males and females in last 12 months prevalence of marijuana use. For both genders, the perceived access to marijuana was the strongest predictor for marijuana use in the last year. In males, age group of 30-65 years had protective effects against the use of marijuana. On the other hand, illegal drug use in the neighborhood, low risk perception of regular use of marijuana and low risk perception of sometime use of marijuana were identified as risk factors. In females, age group of 19 to 29 years and 30 to 65 years were identified as protective factors. Furthermore, low risk perception of sometime use marijuana was determined as predictor of marijuana use. The results show differences and similarities between male and female in identifying gender-specific predictors.